Health Education About Hypertension in The Community in Bingkeng Village, Dayeuhluhur Sub-District, Cilacap Regency - Awaliyah, Cucu Nur; Aprilia, Anisya Bunga; Ubaidillah, Andri; Safitri, Gina Sani; Yunisa, Kathy; Triyansyah, Muhammad Dinar; Hidayah, Tika Nur; Nurul, Tri Hana; Alwi, Rizki Muhamad; Budiana, Rundy; Anggarasari, Nandhini Hudha (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The high case of hypertension is a problem in Indonesia, including in the village of Bingkeng on blood pressure examination there are 16 (53.3%) of 30 people who have hypertension. Checking for hypertension is one of the programs carried out by the Puskesmas and it is carried out regularly to determine the condition of hypertension in the community in Posbindu. This hypertension usually attacks older people. Hypertension in the long term can cause various complications such as stroke, heart attack, heart failure and chronic kidney failure and even death. Although currently there are many effective drugs available for controlling hypertension, but they are still not good, therefore health education is very important to increase knowledge about preventing hypertension. This community dedication aims to provide additional knowledge to the community and elderly caregivers regarding risk factors, signs and symptoms, hypertension prevention and hypertension examination. This community dedication are carried out in August-September 2021 in the village of Bingkeng, especially in the hamlets of Pasirmanggu, Bingkeng and Nambo. 30 participants have participated in health education activities about hypertension. Based on the results of the evaluation after health education activities, most of the community and elderly caregivers understand knowledge related to hypertension, but support is still needed to change healthy lifestyles in the community. Based on the results of visits to check hypertension again, some participants still have hypertension.